2021
DOI: 10.3390/jcm11010008
|View full text |Cite
|
Sign up to set email alerts
|

Common ALDH3A1 Gene Variant Associated with Keratoconus Risk in the Polish Population

Abstract: Background: ALDH3A1 protein is important in maintaining corneal physiology and protecting the eye from UV damage. However, none of the genome-wide association studies has indicated that the ALDH3A1 locus is associated with keratoconus. In this study, we examined the potential role of ALDH3A1 variants as risk factors for keratoconus incidence and severity in a large group of Polish keratoconus patients. Methods: In the first stage we analyzed the coding region sequence of the ALDH3A1 in a subgroup of keratoconu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…In contrast to α-SMA, the expression of ALDH3A1 in quiescent form cornea keratocytes notably reduced, deactivating the pathway to trigger ALDH3A1 under high curvature. ALDH3A1 is a known crystalline protein that maintains the transparency of the cornea stroma 36 . This downregulation of ALDH3A1 in cornea keratocytes under high curvature conditions may be associated with the stromal cloudiness observed in keratoconus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to α-SMA, the expression of ALDH3A1 in quiescent form cornea keratocytes notably reduced, deactivating the pathway to trigger ALDH3A1 under high curvature. ALDH3A1 is a known crystalline protein that maintains the transparency of the cornea stroma 36 . This downregulation of ALDH3A1 in cornea keratocytes under high curvature conditions may be associated with the stromal cloudiness observed in keratoconus.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings show that mechanical stimuli can stimulate TGF-β/Smad2/3 signaling pathways, which can be explained by exploring crosstalk between Rho/ROCK and Smad2/3 pathways 33 34, 35 . Even though recent studies have shown the possible crosstalk between mechanical strain influences the Rho/ROCK pathway 33 and the Smad2/3 signaling pathway 34,35 in lung, kidney, and sclera [33][34][35][36][37][38] , the precise mechanisms by which ROCK influences the expression of TGF-βinduced profibrotic mediators are yet to be uncovered. To accurately determine the impact of these phenotypic changes in corneal keratocytes, further in-depth analyses at the protein and gene levels are required to dissect the signaling pathways involved.…”
Section: Discussionmentioning
confidence: 99%